Coronary microvascular dysfunction is only detectable in type 2 diabetes in the presence of obesity. (14th October 2021) - Chowdhary, A; Thirunavukarasu, S; Jex, N; Bowers, C; Cubbon, R; Xue, H; Kellman, P; Greenwood, J P; Plein, S; Levelt, E
Abstract: Background: Heart failure (HF) is a leading cardiovascular complication of type 2 diabetes (T2D). Coronary microvascular dysfunction (CMD) precedes HF in diabetes and carries important prognostic information. CMD is also evident in metabolically healthy obese individuals without diabetes or hypertension. Whether diabetes causes CMD in the absence of obesity is uncertain. The interrelation among visceral adiposity and CMD has not been assessed previously. Objectives: We sought to better understand the links between visceral and epicardial adipose tissue (VAT and EAT respectively) distribution, insulin resistance with myocardial perfusion, energetics and function in asymptomatic lean (LnT2D) and overweight/obese T2D patients (ObT2D) without cardiovascular disease. Methods: 62 participants [27 Ob-T2D, 15 Ln-T2D, and 20 overweight controls] were recruited. Subjects underwent cardiac and abdominal magnetic resonance imaging and 31P-magnetic resonance spectroscopy, for measurements of EAT and VAT areas, rest and adenosine stress myocardial blood flow (MBF), cardiac function and phosphocreatine to ATP ratio (PCr/ATP). Fasting blood samples were taken for plasma homeostasis model assessment of insulin resistance (HOMA-IR) index calculations. Results: The biochemical characteristics and multiparametric MR results are given in Table 1 and results of Pearson's regression analysis in the entire study population are given in Table 2. Stress MBF was lowest in ObT2D, while rest MBF was highest in LnT2D. Left ventricular ejection fraction (LVEF) and myocardial PCr/ATP were similarly reduced in diabetes groups. In the absence of obesity, there was no significant increase in VAT, EAT or HOMA-IR in T2D patients compared to controls. BMI and VAT, negatively correlated with LVEF, and strain parameters. PCr/ATP correlated with LVEF, but not HOMA-IR. BMI, EAT and VAT all correlated significantly with HOMA-IR, and HOMA-IR correlated with cardiac functional parameters. There was no association between HOMA-IR and myocardial perfusion. Conclusions: In this study CMD was only evident in ObT2D patients, with normal rest and stress MBF in LnT2D patients. Despite normal perfusion and no significant increase in insulin resistance, LVEF and myocardial PCr/ATP were similarly reduced in LnT2D and ObT2D, and PCr/ATP correlated with LVEF. This suggests that alterations in cardiac energy metabolism are mechanistically more relevant for the pathophysiology of diabetic cardiomyopathy in LnT2D patients. In the absence of correlation between insulin resistance and myocardial perfusion, factors like inflammation and altered adipokine profile may play important roles for the pathophysiology of CMD in ObT2D patients. A better understanding of the underlying pathophysiological mechanisms of diabetic cardiomyopathy in LnT2D and ObT2D may help to develop contemporary tailored treatment and prevention strategies to tackle excess heart failure risk. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): BHFWellcome trust